Teknologi Pengeringan Makanan Tradisional Terakusisi Dengan Sensor Arduino Sebagai Alternatif Media Pembelajaran Fisika Yang Selaras Dengan Perkembangan Sistem Otomatisasi - Adi Pramuda; Soka Hadiati; Lia Angraeni (Kappa Journal, 2024)
The use of Arduino integrated sensors for appropriate technology in food processing in West Kalimantan is still very minimal. On the other hand, the quality of food ingredients that are specially dried using conventional drying is very far from health quality standards. This problem is actually very useful for developing more contextual physics education learning media. Moreover, various materials that are currently connected to concrete thermal measurements, for example, do not use measuring instruments that can actually be used in everyday life, especially in food processing technology, so that students are not motivated in learning physics and their learning outcomes are low.The current availability of Arduino and its sensors makes it possible to produce a traditional food drying technology acquired with Arduino sensors that is in line with the physics education study program curriculum. This has not been developed comprehensively in West Kalimantan. The objectives of this research are: 1. Obtain a design for traditional food drying technology acquired with an Arduino sensor which is proven to be effective in terms of energy and drying time; 2. Obtain physics learning media which involves exploring traditional food drying technology acquired with a valid Arduino sensor. This research is included in R & D (Research and Development). This research begins with a design concept which is realized in the form of design construction drawings, the manufacturing process and testing of products that have been made, as well as the design of physics learning tools. The research results show that the traditional food drying technology acquired using an Arduino sensor as a learning medium has been successfully developed and has met the feasibility criteria in the high category